Interkoneksi Materi Aljabar dalam Al Qur'an dan Desain Pembelajarannya pada Siswa SMP (Jurnal Inovasi Pendidikan Matematika (JIPM), 2023)
Numerous researchers have done mathematical analyses of the Qur'an. This research seeks to determine the connection (interrelationship) between algebraic material and the Qur'an and integrate the mathematical learning process into instructional systems, particularly in the connectivity of algebraic information in the Qur'an. This research utilizes qualitative approaches, including content analysis, documentation, and interviews for data collection. Given the wide scope of mathematics, research is limited to verses of the Qur'an, which contain operations of algebraic forms. The tools utilized are interview guides and recording aids. Data analysis comprises the phases of data reduction, data display, and conclusions. The study results indicate an interconnection of algebraic material in the Qur'an, which includes algebraic operations material, namely addition, subtraction, multiplication, and division of algebraic forms. The interconnectivity of algebraic material in the Qur'an can be found in twelve verses. As is well known, there are five paragraphs devoted to the operation of addition of algebraic forms, two to the operation of subtraction of algebraic forms, one to the operation of multiplication of algebraic forms, and four to the operation of the division of algebraic forms. In addition, the earliest mathematics learning design is located in the core of learning grammar as a sort of integration of the Qur'anic content, which becomes the backdrop for learning mathematics, particularly algebraic information.